The Relationship Between Family Environment and School Environment on Discipline of Students’ Majoring in Accounting at the East Jakarta Vocational High School - Anggreani, Raden Andini; Ati Sumiati; Mardi (First Ciera Publisher, 2023)
This study aims to know: (1) relationship between family environment and students’ discipline; (2) relationship between school environment and students’ discipline; and (3) relationship between family environment and school environment on students’ discipline. From all vocational high school in East Jakarta, Researchers took samples from two schools. The reachable population in this study were all students’ that majoring accounting on SMK 48 and SMK 46, totaling of 431 people. With the proportion random sampling technique, the total of sample is 81 students’. The questionnaires that researchers distributed were measured using a Likert Scale. Based on the results of research conducted by researchers on all of three variables, it appears in the results of the calculation of the coefficient of determination (R2), that the percentage of the relationship between the family environment and student discipline is 17%. The percentage of relationship between school environment and students’ discipline is reaches 30.5% and with the coefficient determination test it can be concluded that Family Environment and School Environment simultaneously has a positive relationship on Students’ Discipline by 32%.